Legal Protection of Islamic Banks Against Problematic Murabahah Financing Associated with the Use of Notary Covernote - Sarah Rizki Ramadhan; Masykur, Hamidi; Sigit Nur Rachmat (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Covernote is a certificate from a notary that becomes an important requirement in the disbursement of murabahah financing, especially when the customer has not met the complete requirements, such as the unfinished collateral checking process or the status of the land that still does not have a certificate of ownership. Although it does not have legal force, the Covernote serves as a guideline for Islamic banks in disbursing financing, with the notary responsible for completing the collateral checking process until the issuance of the Deed of Granting Mortgage. Although notaries have the authority to make authentic deeds or deeds under hand, Covernote is not included. This research is important to understand the law related to notary Covernote, the urgency of legal protection for banks in the case of notaries who do not fulfill their obligations, and analysis of legal remedies that can be taken by banks against non-performing loans due to notary negligence in Covernote. The research method used is empirical juridical research, which is a research conducted on the real situation that occurs in the application of legal practice in society and analyzes the actions of legal institutions related to these problems which aim to provide legal certainty. The conclusion obtained is that the quality of financing is the main indicator in assessing the financial health and risks faced by an Islamic bank. The category of financing, ranging from current to non-performing, illustrates the customer's ability to pay obligations in accordance with the agreed contract. Effective monitoring and management of financing is necessary to identify and address risks in a timely manner, minimize financial risks, and maintain the continuity of bank operations